The effect of halotolerant bacteria isolated from saline soil on the growth and yield of maize in saline soil - Nurul Aini; Wiwin Sumiya Dwi Yamika; Nindi Kurniasari; Agung Nugroho; Luqman Qurata Aini (Brawijaya University, 2023)
Salinity is a common problem of abiotic stress in the world. Salinity stress causes yield loss in cultivated crops, such as maize. The yield of maize exposed to salinity stress can be increased with the application of some beneficial microorganisms. Three isolates of halotolerant bacteria from saline fields can potentially be used as biostimulants (plant growth-promoting rhizobacteria). A field experiment to study the effect of halotolerant bacteria isolates application on the growth and yield of maize (Zea mays L.) in saline soil was arranged in a randomized block design with a combination of isolate types and frequency applications, and it was repeated three times. In this study, four bacterial strains used were SN13 (Streptomyces sp.), SN22 (Bacillus megaterium), SN23 (Bacillus sp.) and SN26 (Bacillus aryabhattai) isolated from the soil of saline-prone regions of Lamongan, in coastal East Java, Indonesia. Results indicated that an application of halotolerant bacteria was able to improve the yield and nutrient uptake of maize in saline soil. However, the application of halotolerant bacteria significantly improved leaf total chlorophyll content (105.94%), plant dry weight (56.14%), Grain weight per cob (108.11%) and had a positive trend in increasing N uptake (61.19%), and Na uptake (73.09%) compared to control. It is concluded that the application of halotolerant bacteria is able to alleviate the salinity stress of maize in saline soil.